Pénz, pénz! Beszélgetés az Angelica kávéházban
Róbert Burgert agronomist, Tamás Ungvári critic and university professor, Ervin Auber restaurant owner, Péter Zwack businessman and politician, money, securities, cash, making and having money program host Péter Rózsa Péter Gárdos